ADHERENCE TO A COMPREHENSIVE REHABILITATION PROGRAM AFTER CORONARY ARTERY BYPASS GRAFTING: A CHALLENGE FOR A PATIENT OR A PHYSICIAN? - Помешкина, Светлана Александровна; Беззубова, Валентина Анатольевна; Аргунова, Юлия Александровна; Барбараш, Ольга Леонидовна (Medicine in Kuzbass, 2018)
Aim – to assess the awareness of patients referred to elective coronary artery bypass grafting (CABG) about cardiac rehabilitation programs and to evaluate the adherence of cardiologists to appoint exercise outpatient cardiac rehabilitation to CABG patients. Methods. 124 patients with stable coronary artery disease were surveyed to estimate their awareness about postoperative cardiac rehabilitation program and its structure as well as their wishes to participate in these programs. 44 cardiologists were surveyed to evaluate their awareness of exercise cardiac rehabilitation programs after CABG. Results. Most patients were confident in the need of cardiac rehabilitation, but a few of them participated in the cardiac rehabilitation programs. One of the major reasons for patients’ poor adherence to exercise cardiac rehabilitation is insufficient knowledge on the indications and contraindications to exercise outpatient rehabilitation. In addition, cardiologists had insufficient knowledge on the effectiveness of exercise cardiac rehabilitation resulting in a high rate of patients’ refusal to participate in these programs. Conclusion. Patients’ motivation for treatment and its retention for a long-term period may require specific patient education to raise their awareness about cardiac rehabilitation. In addition, physicians’ adherence to the appointment of exercise cardiac rehabilitation programs should be improved.